Risk of drug-related upper gastrointestinal bleeding in the total population of the Netherlands: a time-trend analysis - Frits R Rosendaal; Albert Dahan; Ajda Bedene; Eveline L A van Dorp; Willem M Lijfering (BMJ Open Gastroenterology)
Objective Many prescribed and over-the-counter medications, for example, non-steroidal anti-inflammatory drugs (NSAIDs) are associated with upper gastrointestinal bleeding (UGIB). Recently, a decrease in prescribing of NSAIDs was observed in the Netherlands, but whether a similar decreasing trend could be observed in the incidence of severe UGIB (either fatal or requiring hospitalisation), contingent on medication prescription, is unknown.Design We conducted a cohort study using Dutch national statistics on pharmacy claims, hospitalisation and mortality between 2013 and 2018. We explored the incidence of sex-specific and age-specific severe UGIB in four (sub)populations: (A) total population, (B) without a filled prescrption for NSAIDs, (C) without filled prescriptions for NSAIDs and antithrombotic agents, (D) without any risk factors for UGIB.Results The cumulative incidence of severe UGIB did not decrease throughout the study period, regardless of the subgroup analysis. In the total population, it was 199 per 100 000 inhabitants (95% CI 197 to 201) in 2013–2014 and 260 (95% CI 258 to 263) in 2017–2018. The absolute risk of severe UGIB was 50% lower in the subgroup B than in the full cohort. It decreased further by 50% in the subgroup D when compared with subgroup B. The risk of severe UGIB was 1.5–1.9 fold higher in young women than in young men; an indication of over-the-counter NSAIDs use being more prevalent in women than men in this age group.Conclusion We found no evidence to support a relationship between reduced prescribing of NSAIDs and the incidence of severe UGIB in the Netherlands since 2013. The relationship was also not observed when we removed the effect of risk factors.